The tide forecasting system for China coastal seas: A case study on the effect of tides on storm surge - Zhao, Yifei; Deng, Zengan; Zhai, Jingsheng; Yu, Ting; Wang, Hu; Cao, Yu; Tong, Yanbin (Kuwait Journal of Science, 2019)
A Tide Forecasting and Visualization System (TFVS) is developed for providing the tidal information service in China coastal regions. TFVS is capable of forecasting the tides (conducting harmonic analysis on the contrast) by invoking the T_TIDE package. Tide forecasting at 4 tidal stations have been carried out. Results show that the forecasted tides agree well with the observations, which validates the accuracy and reliability of TFVS. Both forecasted and observed tides can be visualized and analyzed on TFVS. The realistic status of tides along China coastal region can be directly perceived/monitored on TFVS. In addition, TFVS provides reliable tidal data to oceanographic community and further support science-based decision-making (such as disaster mitigation) to local government. By utilizing tidal data form TFVS, case study of storm surge in coastal region of Jiangsu Province is carried out to detect the proportion between maximum astronomical tides and storm-induced water rise (storm surge) in storm situations. It is shown that the average proportion of maximum astronomical tide in the highest total water level in Jiangsu Province is about 70%.